Kam Sweet Rice (Oryza sativa L.) Is a Special Ecotypic Rice in Southeast Guizhou, China as Revealed by Genetic Diversity Analysis - Liu, Chunhui; Cui, Di; Jiao, Aixia; Ma, Xiaoding; Li, Xiaobing; Han, Bing; Chen, Huicha; Ruan, Renchao; Wang, Yanjie; Han, Longzhi (Frontiers in Plant Science, 2022)
Kam Sweet Rice (KSR) is a special kind of rice landrace that has been domesticated for thousands of years by the local Dong people in southeast Guizhou province, China. KSR has many distinguishing characteristics including strong fragrance; high resistance to diseases, pests, and adverse abiotic conditions; difficulty of threshing; and glutinous texture. There is a lack of systematic research on its genetic diversity. In this study, we analyzed the levels and patterns of genetic diversity and nucleotide variation in 1,481 rice genomes using simple sequence repeat (SSR) markers and single nucleotide polymorphism (SNP) haplotype analysis of six unlinked nuclear loci. The accessions included 315 KSR resources from southeast Guizhou, 578 rice landraces from six rice-growing ecological zones in Guizhou, 546 rice landraces from nine provinces around Guizhou, and 42 wild rice sources. Genetic diversity and heterozygosity of KSR were both low, and thus KSR might be close to a pure rice line. Population structure analysis showed that KSR was isolated into a single type of rice, which had a large genetic distance and a unique genetic background compared to the local varieties in Guizhou province, indicating that KSR is a special rice ecotype. Large-scale sequencing showed that the population of KSR was rich in haplotypes for resistance to bacterial blight (Xa23) and rice blast (Pid3), and identified unique haplotypes that were different from those of the six rice ecotypes in Guizhou. This study shows that KSR is an excellent rice germplasm resource, provides important information for the improvement and utilization of rice landraces, and serves as a reference for formulating effective rice conservation measures.